Does methylprednisolone reduce the mortality risk in hospitalized COVID-19 patients? A meta-analysis of randomized control trials. (3rd August 2021) - Hasan, Syed Shahzad; Kow, Chia Siang; Mustafa, Zia Ul; Merchant, Hamid A.
ABSTRACT: Objectives : The question remained if mortality benefits with dexamethasone seen in patients with coronavirus disease 2019 (COVID-19) also extend to other systemic corticosteroids such as methylprednisolone. This article presents a meta-analysis of randomized controlled trials (RCTs) to ascertain if methylprednisolone can be recommended for use in patients with COVID-19 to prevent deaths. Methods : Systematic literature search was performed in PubMed, Scopus, Cochrane Central Register of Controlled Trials, and preprint servers until 13 April 2021. The outcome of interest was all-cause mortality. The random-effects model for the meta-analysis was utilized to estimate the pooled odds ratio (OR) at 95% confidence intervals (CI). Results : Five RCTs were included in the meta-analysis. The pooled OR for all-cause mortality was 0.64 (95% CI: 0.29 − 1.43, n = 652) comparing methylprednisolone with the control, indicating no mortality benefits. A similar finding was noted with a sub-group analysis including four trials that used low-dose methylprednisolone. However, the only trial that administered high dose methylprednisolone indicated a statistically significant mortality benefit (OR 0.08, 95% CI: 0.02–0.42). Conclusions : In determining equipotent doses for an acute short-course pulse therapy of corticosteroids, the biological half-life of steroids should also be accounted for besides the potency factor. A short duration (3–5 days) pulse therapy of high-dose methylprednisolone can be a promising alternative to the low-dose dexamethasone therapy in severely ill patients with COVID-19 to prevent deaths.